Front Cover: Barium‐Catalysed Dehydrocoupling of Hydrosilanes and Borinic Acids: A Mechanistic Insight (Chem. Eur. J. 16/2020). Issue 16 (10th February 2020) - Le Coz, Erwann; Zhang, Ziyun; Roisnel, Thierry; Cavallo, Luigi; Falivene, Laura; Carpentier, Jean‐François; Sarazin, Yann
Abstract : The mechanism of the barium‐catalysed dehydrocoupling between borinic acids R2 BOH and hydrosilanes HSiR'3 that generate borasiloxanes R2 BO‐SiR'3 has been elucidated by teams at ISCR Rennes (France) and KAUST (Saudi Arabia) upon combination of experimental and computational data. The analysis shows that these chemoselective reactions are mediated by dinuclear catalytically active barium‐boryloxide species, regardless of the actual nuclearity of the precatalyst, monomeric as in [Ba(OB{CH(SiMe3 )2 }2 )2 ], or dimeric as in [Ba{N(SiMe3 )2 }OB{CH(SiMe3 )2 }2 ]2 and [Ba{N(SiMe3 )2 }2 ]2 . More information can be found in the Full Paper by L. Falivene, Y. Sarazin et al. on page 3535 .